Eczacılıkta Güncel Araştırmalar III-Güz - Küçük, Ege; Akman, Tuğrul Çağrı; Dehri, Ömer Faruk; Sevinç Özakar, Rukiye; Özakar, Emrah; Alparslan, Bayram; Özçelik, İbrahim; Özdal, Zeliha Duygu; Yıldıztekin, Kübra Gizem; Vural, Meltem; Küçük, İrem Sena; Türkmen, Neşe Başak; et al. (2024)
-